2008
DOI: 10.1177/0009922808318340
|View full text |Cite
|
Sign up to set email alerts
|

Social Influences on Self-Reported Physical Activity in Overweight Latino Children

Abstract: Psychosocial variables influence physical activity for different age groups, sex, and ethnic groups. However, little is known about their influence on physical activity in preadolescent Latino children. The authors examined how a) confidence in one's ability to be physically active (selfefficacy); b) ideas about the consequences of being physically active (beliefs), and c) the influences of family and friends on physical activity (social influences) effect physical activity levels in overweight (body mass inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…[32] Within Latino children however, social support from friends and family is significantly and positively correlated with physical activity. [33] Given that social support for physical activity is a primary predictor of activity levels over time in youth[34] and social support is an important predictor of health-related QoL in obese youth[35], we believe this construct may be a critical theoretical mechanism underlying improvements in health behaviors and outcomes. Social support will be assessed using the PACE + Physical Activity and Diet Survey for Adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…[32] Within Latino children however, social support from friends and family is significantly and positively correlated with physical activity. [33] Given that social support for physical activity is a primary predictor of activity levels over time in youth[34] and social support is an important predictor of health-related QoL in obese youth[35], we believe this construct may be a critical theoretical mechanism underlying improvements in health behaviors and outcomes. Social support will be assessed using the PACE + Physical Activity and Diet Survey for Adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…In fact the Latino cultural notion of respeto (respect), seems consistent with this interpretation. 26 Another explanation derives from our prior work, 12 where we noted that social influences significantly predicted self-reported baseline physical activity for Latino parent- preadolescent child dyads. Studies of Latino adults have demonstrated the importance of social and family support.…”
Section: Discussionmentioning
confidence: 95%
“…9 Psychosocial determinants (such as, self-efficacy and social influences,) influence physical activity in African-American and White populations, 9-11 however, limited data exist on what works with Latinos. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, overweight and obese girls did not meet the recommended number of steps/day for their age. The lack of social support from adults and peers for overweight girls can negatively affect the practice of PA, as indicated by a study performed by Gesell 22 . In this regard, modeling and vicarious processes are the fundamental means by which children´s behavior is acquired and existing patterns may be modified driving self-efficacy for PA 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, little research has been done to identify differences and key actors of Hispanic children´s social networks in different contexts or settings 21,22 . Therefore, the aim of this study is to identify the structure of the social networks pertaining to the practice of structured and unstructured PA by Mexican children, in both the school and the community contexts.…”
Section: Introductionmentioning
confidence: 99%